1982
DOI: 10.1111/1523-1747.ep12497845
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lipids on the Aggregation and Permeability of Human Stratum Corneum

Abstract: The role of stratum corneum (SC) constituents in SC barrier properties was assessed directly in vitro in a reaggregated system. Fragments of SC from the sole of the foot (hyperplastic tissue) and from the calf (normal tissue) were reduced, separately, to individual cells and these cells were depleted of lipids by solvent extraction. Lipids taken from the cells themselves or from SC from other areas of the body were then added to the cells. None of the fractions used allowed for reaggregation of plantar SC cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…In the stripped skin studies, the formulation vehicle seemed to have little impact. It has been widely reported that the stratum corneum represents a major barrier to transdermal permeability (Scheuplein and Blank, 1973;Smith et al, 1982;Madison et al, 1987), and as expected, transdermal fluxes of PS were greater through stripped skin than intact skin. Because the barrier integrity of the stratum corneum may be compromised with age and because AD is an age-associated disease, the former was assessed to provide an estimate of maximal permeability.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In the stripped skin studies, the formulation vehicle seemed to have little impact. It has been widely reported that the stratum corneum represents a major barrier to transdermal permeability (Scheuplein and Blank, 1973;Smith et al, 1982;Madison et al, 1987), and as expected, transdermal fluxes of PS were greater through stripped skin than intact skin. Because the barrier integrity of the stratum corneum may be compromised with age and because AD is an age-associated disease, the former was assessed to provide an estimate of maximal permeability.…”
Section: Discussionsupporting
confidence: 68%
“…1) was used (Addicks et al, 1987;Sclafani et al, 1993) to assess the availability of PS from vehicle, and subsequent transdermal permeability. Because the stratum corneum has been characterized as a major barrier to transdermal permeability (Sheuplein and Blank, 1973;Smith et al, 1982;Madisonet al, 1987) and barrier integrity may be variably affected by age (Ghadially et al, 1995), permeabilities were investigated through both intact and tape-stripped skin. Intact skin or tape-stripped skin was isolated from the back of hairless mice and placed between the donor and the acceptor phase of the flow-through cell, allowing a permeation surface area of 1 cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…12, 14). Preliminary evidence also suggests that stratum corneum lipids may be essential for the invisible, orderly process of normal desquamation (15,16 (2). Moreover, the diagnosis ofRXLI was confirmed by prior assay of steroid sulfatase activity in fibroblasts and /or leukocytes (6) (Table I).…”
Section: Introductionmentioning
confidence: 99%
“…It also prevents the uptake of water into animal body, stbilizes the body temperature and also serve as a barrier to chemical and biological attack from the environment. Vast attention has been directed to the water transport through the stratum corneum [3][4][5][6] . Most evidences indicate that the lipids content of the stratum corneum to be the main factor in the stratum corneum barrier to trans dermal …”
Section: Stratum Corneummentioning
confidence: 99%